2018
DOI: 10.11646/phytotaxa.367.3.3
|View full text |Cite
|
Sign up to set email alerts
|

Desmonostoc danxiaense sp. nov. (Nostocales, Cyanobacteria) from Danxia mountain in China based on polyphasic approach

Abstract: The recently established genus Desmonostoc was characterized by forming macroscopic colonies with diffluent mucilaginous envelopes embedding long vegetative filaments and possessing long chains of akinetes. The establishment of this new genus was further supported by the clustering of the 16S rRNA gene, which have a distinctive phylogenetic placement outside of Nostoc. In this study, a new cyanobacterial species was isolated from a wet rocky wall in Danxia mountain, Guangdong province, southern China, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…8). The secondary structure of the D1-D1′ helix region of SA14 was also compared with the structures from de Alvarenga et al [24] and Cai et al [25] and it was observed that D1-D1′ helix region of SA14 had a considerably different structure. Finally, the folded secondary structure of the D1-D1′ helix region was obtained for SA10 and compared with the available structures from members of the genus Desikacharya.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…8). The secondary structure of the D1-D1′ helix region of SA14 was also compared with the structures from de Alvarenga et al [24] and Cai et al [25] and it was observed that D1-D1′ helix region of SA14 had a considerably different structure. Finally, the folded secondary structure of the D1-D1′ helix region was obtained for SA10 and compared with the available structures from members of the genus Desikacharya.…”
Section: Resultsmentioning
confidence: 99%
“…While morphological, molecular and phylogenetic evidence were strong indicators of the taxonomic positioning and novelty, to further ascertain the taxonomic status of our strains, we performed the 16S-23S ITS folded secondary structure analysis as it has been reported to be an effective tool in differentiating the members of the genera Aliinostoc, Desmonostoc and Desikacharya [4,6,12,[23][24][25]. Secondary structures corresponding to the D1-D1′ helix region and BoxB region were obtained for all the members of the genus Aliinostoc.…”
Section: Resultsmentioning
confidence: 99%
“…5K). The base stem of Compactonostoc have been largely performed (Song et al 2015a, 2015b, Li and Li 2016, Li et al 2017, Cai et al 2018, 2019a, 2019b, Wang et al 2019). The present study described Violetonostoc as a new cyanobacterial genus isolated from the Small Seven-hole Scenic Area in Guizhou province, and this is the second new Nostoc-like genus from the same site, following the first new one as Minunostoc (Cai et al 2019a).…”
Section: Its Secondary Structuresmentioning
confidence: 99%
“…The study of terrestrial Nostoc-like cyanobacteria in China was limited till recent years, during a broader survey on Chinese terrestrial Nostoc-like cyanobacteria, we have found and described several new genera and species in the family Nostocaceae (Cai et al 2018(Cai et al , 2019a(Cai et al , 2019b(Cai et al , 2020a(Cai et al , 2020b. In this study, we isolated morphologically distinct heterocytous cyanobacteria from seldomly sampled regions in China, such as Baishan city in Jilin province and Shennongjia Forestry District in Hubei province.…”
Section: Introductionmentioning
confidence: 98%